Sistem Pendukung Keputusan Untuk Menentuan Desa Paling Maju dengan Menggunakan Metode MOORA - Rifqi Naufal Fajrul Mubaroq; Evita Dwi Prasanti; Yuni Novita Br. Sihaloho; Edoardus Dwijo Wijayanto; Akhmad Fauzi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Decision Support System (DSS) is an approach to support decision making using data, provides an easy interface, and can incorporate the thinking of decision makers. In this study, we take a case study that can be solved by using a decision support system, where the problem faced by the Government of the Sub-District of Sumbang is how to determine the most advanced village in the District of Sumbang, because to do a selection one must use the manual method and the assessment process takes a long time to get. results. Therefore, a decision support system is made that can assist the assessment process and where the decision support system is carried out using the moora method. Based on the results of calculations regarding research in determining the most advanced village in the Contributing Regency is the Contributing Village with a value of 0.3758. Where the village has very good road conditions and the facilities available in the village are also very good compared to other villages.